A Methoxydiphenylamine‐Substituted Carbazole Twin Derivative: An Efficient Hole‐Transporting Material for Perovskite Solar Cells1. Issue 39 (16th July 2015) - Gratia, Paul; Magomedov, Artiom; Malinauskas, Tadas; Daskeviciene, Maryte; Abate, Antonio; Ahmad, Shahzada; Grätzel, Michael; Getautis, Vytautas; Nazeeruddin, Mohammad Khaja
Abstract The small‐molecule‐based hole‐transporting material methoxydiphenylamine‐substituted carbazole was synthesized and incorporated into a CH3NH3PbI3 perovskite solar cell, which displayed a power conversion efficiency of 16.91 %, the second highest conversion efficiency after that of Spiro‐OMeTAD. The investigated hole‐transporting material was synthesized in two steps from commercially available and relatively inexpensive starting reagents. Various electro‐optical measurements (UV/Vis, IV, thin‐film conductivity, hole mobility, DSC, TGA, ionization potential) have been carried out to characterize the new hole‐transporting material.